2020
DOI: 10.3389/fphys.2020.00624
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Animal Models for Arrhythmogenic Cardiomyopathy

Abstract: Arrhythmogenic cardiomyopathy has been clinically defined since the 1980s and causes right or biventricular cardiomyopathy associated with ventricular arrhythmia. Although it is a rare cardiac disease, it is responsible for a significant proportion of sudden cardiac deaths, especially in athletes. The majority of patients with arrhythmogenic cardiomyopathy carry one or more genetic variants in desmosomal genes. In the 1990s, several knockout mouse models of genes encoding for desmosomal proteins involved in ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 244 publications
(400 reference statements)
0
35
0
3
Order By: Relevance
“…In 2002, Eshkind et al demonstrated that the global homozygous knock-out of Dsg2 in mice is embryonic lethal [ 43 ]. Therefore, different conditional knock-out, knock-in, and transgenic mouse models for Dsg2 leading to murine arrhythmogenic cardiomyopathies have been developed [ 44 , 45 , 46 , 47 , 48 , 49 ]. In spite of this, the first pathogenic DSG2 mutations associated with ACM in humans were found in 2006 [ 37 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 2002, Eshkind et al demonstrated that the global homozygous knock-out of Dsg2 in mice is embryonic lethal [ 43 ]. Therefore, different conditional knock-out, knock-in, and transgenic mouse models for Dsg2 leading to murine arrhythmogenic cardiomyopathies have been developed [ 44 , 45 , 46 , 47 , 48 , 49 ]. In spite of this, the first pathogenic DSG2 mutations associated with ACM in humans were found in 2006 [ 37 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although these mice carry the same mutations observed in boxer dogs and humans, their phenotype is not identical: no fat infiltration is generally observed in the rodent heart myocardium. In addition, transgenesis techniques are more successful in reproducing loss of function than missense mutations ( 73 ).…”
Section: Modeling Of Congenital Heart Diseasesmentioning
confidence: 99%
“…Animal models are essential for understanding molecular pathways, and several have been utilized to study TTNtv including a mouse model with an A-band truncation mutation, and zebrafish models that have several different truncation variations [ 39 , 40 , 41 , 42 ]. A review of these important models has been recently carried out [ 43 ].…”
Section: Truncation Mutations In Ttn Cause Dilamentioning
confidence: 99%
“…This is also demonstrated in animal models including a rat knockout of RBM20 [ 60 ]. Further animal models for RBM20 and its targets have been described but are not as well characterized [ 43 ]. The preference for the longer, softer N2BA isoform in RBM20 mutants results in decreased active and passive tension of cardiomyocytes contributing to dilation of the ventricle [ 68 ].…”
Section: Titin Transcriptional Modifications Are Associated With Dmentioning
confidence: 99%